Impact of Management Ethics on Payment Discipline - Tanja Šalomon; Maja Meško (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
A company's ethics is one of the key factors of its effectiveness. Having poor business ethics usually lead to the lack of payment discipline. The main purpose of the study was to identify the possible impact of management ethics on the financial discipline of companies. The study involved 273 Slovenian public and private companies, which represented 9.1% of all companies invited to take part in the survey. The data on management ethics were collected using the Corporate Ethical Virtues measurement instrument questionnaire and the data concerning average late payments were obtained from the database of the Slovenian rating agency “I d.o.o.”. Statistical analysis was carried out using SPSS 20.0 for Windows. We conducted a factor analysis and a regression analysis using the stepwise method. We found that management ethics has a positive impact on payment discipline. At the end of the article, we give suggestions for improvement of payment discipline.
Keywords: M14; G02; 330; payment discipline; late payments; ethic; management ethics; Slovene companies